2022
DOI: 10.1021/acsearthspacechem.2c00255
|View full text |Cite
|
Sign up to set email alerts
|

NOM-Induced Dissolution of CrxFe1–x(OH)3 Precipitates and Formation of Cr(III)-NOM-Fe Colloids under Oxic and Anoxic Conditions

Abstract: Mixed Cr(III)–Fe(III) (hydr)oxides (Cr x Fe1–x (OH)3) are common reduction products of Cr(VI) that have long been considered as the sink of Cr in subsurface environments. While current field and laboratory studies have demonstrated that natural organic matter (NOMox) can dissolve Cr x Fe1–x (OH)3 under oxic conditions, much less is known regarding the dissolution of Cr x Fe1–x (OH)3 by reduced NOM (NOMred) and geochemical behaviors of released Cr(III) under anoxic conditions, which limited our ability to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Upon reaction of Cr(VI) with Fe(II)-HA colloids under anoxic conditions, Cr was completely reduced and formed highly stable Cr(III)-HA-Fe colloids that persisted for at least 20 days, without substantial changes in particle size. 254,255 Mn is considered to be predominantly present as soluble Mn(II) in anoxic environments and in particulate form (Mn(III/IV)) in oxic environments, but several studies have also observed Mn(III) colloids in anoxic environments. 173,256−258 Due to the strong affinity of Mn(III) with NOM, up to 90% of the Mn(III) in anoxic systems can be in colloidal form, and this fraction can increase with increasing molar C/Mn ratios.…”
Section: Impact On Strain and Size Of Redox-generatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon reaction of Cr(VI) with Fe(II)-HA colloids under anoxic conditions, Cr was completely reduced and formed highly stable Cr(III)-HA-Fe colloids that persisted for at least 20 days, without substantial changes in particle size. 254,255 Mn is considered to be predominantly present as soluble Mn(II) in anoxic environments and in particulate form (Mn(III/IV)) in oxic environments, but several studies have also observed Mn(III) colloids in anoxic environments. 173,256−258 Due to the strong affinity of Mn(III) with NOM, up to 90% of the Mn(III) in anoxic systems can be in colloidal form, and this fraction can increase with increasing molar C/Mn ratios.…”
Section: Impact On Strain and Size Of Redox-generatedmentioning
confidence: 99%
“…Pan et al observed the formation of stable colloids (1200 nm) composed of Cr­(III), NOM, and Fe­(III) during Cr­(VI) removal via electrocoagulation at pH 8.0, but below pH 6.0 they aggregated and settled out of the aqueous phase. Upon reaction of Cr­(VI) with Fe­(II)-HA colloids under anoxic conditions, Cr was completely reduced and formed highly stable Cr­(III)-HA-Fe colloids that persisted for at least 20 days, without substantial changes in particle size. , …”
Section: Geochemical Controls Over Colloidal Composition Stability Ag...mentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Furthermore, the redox reactions between OM and Fe at redox interfaces can substantially influence the transport of a colloid and its ability to carry pollutants. [39][40][41][42][43] Previous research has confirmed that Fe-OM colloids can act as vehicles for As(V), Cr(VI), and U(VI) transport. 42,44 However, there is no comprehensive evaluation on the co-transport of FH-OM colloid-loaded Sb.…”
Section: Introductionmentioning
confidence: 98%